The challenges of the Peruvian Civil Code in the metaverse - Vásquez Palacios , María Celeste (Revista de Derecho, 2024)
The main objective of this essay is to analyse the challenges faced by the Peruvian Civil Code in the face of the advance of cyberspace and, in particular, the metaverse. It aims to identify how this body of law must evolve in order to respond to the new technological realities and to ensure adequate protection of rights in the digital environment. The research is carried out from a positivist approach and employs a documentary methodology, based on doctrinal, jurisprudential and normative analysis. The essay contains a brief explanation of the history of the normative body, jurisprudential and doctrinal development, providing a historical and legal context for the understanding of current problems. Then, for a better understanding, some figures that make this type of technology possible will be identified, as well as the repercussions on various legal institutions together with proposals for amendments. Concluding with the planning of critical questions on the challenge that the metaverse represents for the Peruvian Civil Code and invites reflection on the need to update and adapt current regulations to maintain the coherence and effectiveness of the Law in constant progress.